2022
DOI: 10.1177/02692163221099116
|View full text |Cite|
|
Sign up to set email alerts
|

The utility of the surprise question: A useful tool for identifying patients nearing the last phase of life? A systematic review and meta-analysis

Abstract: Background: The surprise question is widely used to identify patients nearing the last phase of life. Potential differences in accuracy between timeframe, patient subgroups and type of healthcare professionals answering the surprise question have been suggested. Recent studies might give new insights. Aim: To determine the accuracy of the surprise question in predicting death, differentiating by timeframe, patient subgroup and by type of healthcare professional. Design: Systematic review and meta-analysis. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 108 publications
0
26
1
1
Order By: Relevance
“…Another strength of this study was that each patient was evaluated by one nurse and one physician involved in the care of the patient and familiar with the history, the patient's clinical trajectory, and the treatment. In other studies evaluating the SQ, one or few physicians and/or nurses have evaluated many, and sometimes all patients at one dialysis unit 28,43 which may introduce a risk of rater bias. 18,31 Limitations include that the nurses responded both to the SQ and to the performance status, and that the physicians in most cases responded both to the CCI and the SQ for their patients.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Another strength of this study was that each patient was evaluated by one nurse and one physician involved in the care of the patient and familiar with the history, the patient's clinical trajectory, and the treatment. In other studies evaluating the SQ, one or few physicians and/or nurses have evaluated many, and sometimes all patients at one dialysis unit 28,43 which may introduce a risk of rater bias. 18,31 Limitations include that the nurses responded both to the SQ and to the performance status, and that the physicians in most cases responded both to the CCI and the SQ for their patients.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…28,29 It has also been evaluated for predicting mortality, as well as to identify patients approaching the end of life and being in need of serious illness conversations. 28,29 In a recent review, 29 the SQ, as a single question or in combination with other variables, was found to be the most common way to identify patients for serious illness conversations. It has also been proposed to be used by different professions in foreseeing the need of serious illness conversations and end of life dialogs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A meta-analysis of the surprise question was recently published. 21 The below table is a modification of the article’s Table 1 with added positive likelihood ratios (PLRs) and negative likelihood ratios (NLRs) for the various patient subgroups. We believe that the addition of this interpretation will greatly enhance the understanding of trial results.…”
Section: Definitionsmentioning
confidence: 99%